Learn iOS 11 Programming with Swift 4 : Learn the fundamentals of iOS app development with Swift 4 and Xcode 9. - Clayton, Craig (Packt Publishing, 2018)
You want to build iOS applications for iPhone and iPad but where do you start? Forget sifting through tutorials and blog posts; this book is a direct route into iOS development, taking you through the basics and showing you how to put the principles into practice. With every update, iOS has become more and more developer-friendly, so take ...